Influence Fintech And Digitalization To Performance MSMEs - Halim Setiawan; Ni Putu Widhia Rahayu (International Journal of Economics, Business and Innovation Research, 2024)
Majority performance finance MSMEs in Kemiling Not yet maximum Because not using fintech in process his business. Study This aim For researching the influence of fintech in MSMEs Which is at in Kemiling. In this digital era, MSMEs face new challenges to utilize digital technology to develop their business, but there are still many MSME players who do not understand the use of digital due to the lack of literacy in technology in this era of digitalization. MSME performance is the result of overall success during a certain period contained in the work results, targets, targets and criteria that have been determined and agreed upon together. Approach study used in study This that is study quantitative with use SPSS analysis tool. The population used in this research is SMEs in Subdistrict Kemiling with sample as much 50 respondents. Collection technique data use questionnaire on line Which spread through whatsapp. The tests carried out are data quality tests, classical assumption tests, and multiple linear tests. Results study This is fintech And digitalization has a positive effect and significantly to the performance of MSMEs both partially and jointly.